Meet Addy : an American girl - Porter, Connie Rose, 1959-; Rosales, Melodye (Middleton, Wis. : Pleasant Co., 1993)
In 1864, after her father and brother are sold to another owner, nine-year-old Addy Walker and her mother escape from their cruel life of slavery in North Carolina to freedom in Philadelphia
"Ages 7 and up"--Cover p. [4]
700
Accelerated Reader AR
Keywords: African Americans -- Juvenile fiction; Slavery -- Juvenile fiction; Underground Railroad -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction